APPLICATION OF NOVEL NATURAL POLYMER FOR CONTROLLING THE RELEASE OF FENOVERINE FROM CONTROLLED RELEASE MATRIX TABLETS - Kulkarni, Ajit; Mandhare, Trushali; Aloorkar, Nagesh (International Journal of Applied Pharmaceutics, 2017)
Objective: To explore a novel natural polymer, pullulan for controlling the release of fenoverine from matrix tablets and to elucidate the release kinetics of fenoverine from pullulan and HPMC matrices. Methods: In this study we formulated monolithic matrix tablets containing of fenoverine as controlled-release tablets by direct compression using pullulan, HPMC (Hydroxypropyl methyl cellulose) K4M and HPMC K100M polymers and evaluated for hardness, thickness, friability, weight variation drug content, in vitro drug release characteristics and FTIR (Fourier transform infrared spectroscopy) and DSC (Differential scanning calorimetry) study. Results: All the formulations showed compliance with pharmacopoeial standards. FTIR and DSC study indicated the absence of interaction between fenoverine and excipients. The formulation was optimized on the basis of acceptable tablet properties and in vitro drug release. The results of dissolution studies indicated that the formulation F5 [drug to polymer 1: 0.35] exhibited highest % cumulative drug release of 96.82Â±0.75 % at the end of 12 h. Optimised batch F5 showed super case II transport mechanism and followed zero order release kinetics. Short-term stability studies of the optimized formulation indicated that there were no significant changes observed in hardness, drug content and in vitro dissolution studies at the end of three months period. Similarity factor f2 was found to be 89, which indicated similar dissolution profiles before and after stability study. Conclusion: Based on above results we conclude that pullulan can be used as a polymer for retarding the release of drug from matrix formulations. Keywords: Pullulan, Fenoverine, Hydroxypropyl methyl cellulose, Controlled release, In vitro